Alternative Dispute Resolution and Research Misconduct - Guenin, Louis M. (Cambridge quarterly of healthcare ethics, 1997)
“Any bad settlement,” the wise patent litigator Elmer S. Albritton once observed, “is better than a good lawsuit.” Given the notorious strain of court proceedings and the recognition that settlement does not always prove attainable, a popular movement has recently arisen in favor of “alternative dispute resolution” (or ADR). Indeed it has seemed to many who have participated as committee members, witnesses, or respondents in scientific misconduct cases that there ought to be some method of resolving such matters that is less vexing than traditional adjudication.